Background of the Rivalry between Gheorghiu-Dej and Pauker - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Item based on interviews conducted with defectors and immigrants in Western refugee camps and immigration offices, or Western travelers returning from stays in East European communist countries, supplemented with information collected through Radio Free Europe (RFE) correspondence with anonymous sources from behind the Iron Curtain. This item was transmitted from the Athens field office. This field report was assigned the following topical and geographical subject headings by the RFE/RL: Romania; State Apparatus -- Government; Communist Parties -- Inner Life